KESEJAHTERAAN SOSIAL (AL-‘ADLUL IJTIMA’I) DALAM PERSPEKTIF AL-QUR’AN - Waryono Abdul Ghafur (AN NUR: Jurnal Studi Islam, 2011)
The Qur’an is not only a guiding book that teaches how to worship to Allah, but alsoteaches how human beings live in peace and prosperity. Therefore, worship in Islam isalways integrative although its nature and work are separated. The Qur’an clearly statesthat telling a lie in having a religion –if mahdah worship (Pure worship that has a directrelationship between human and Allah) –stops at the worship. In Islam there is always arelationship between the worldly and the hereafter (ukhrawi) or between the profane andthe sacred. It is a universal paradigm of the Qur’an, especially for enhancing the human’sdegree experiencing social problems, so they do not meet their fundamental needs andcannot achieve their social welfare. Social welfare is one of the main visions that arecarried by the Qur’an and the Prophet Muhammad makes it happen.Kesejahteraan sosial